(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Corruption remains among the most consequential challenges confronting governments and public institutions, undermining economic development, eroding social trust, and weakening political stability. In response, New Public Management (NPM) has been advanced as a prominent reform approach in public administration and public management. Drawing selectively on private-sector logics and instruments, NPM seeks to improve efficiency and effectiveness in public service delivery and to strengthen administrative performance through measures such as decentralization, contracting-out, enhanced accountability, performance measurement, modern managerial techniques, and the institutionalization of sound governance principles. While NPM does not constitute a comprehensive anti-corruption strategy on its own, its emphasis on results, transparency-oriented controls, and audit and evaluation practices is frequently presented as supportive of integrity and anti-corruption objectives.